2014
DOI: 10.1111/1556-4029.12603
|View full text |Cite
|
Sign up to set email alerts
|

Ink Dating Using Thermal Desorption and Gas Chromatography/Mass Spectrometry: Comparison of Results Obtained in Two Laboratories

Abstract: An ink dating method based on solvent analysis was recently developed using thermal desorption followed by gas chromatography/mass spectrometry (GC/MS) and is currently implemented in several forensic laboratories. The main aims of this work were to implement this method in a new laboratory to evaluate whether results were comparable at three levels: (i) validation criteria, (ii) aging curves, and (iii) results interpretation. While the results were indeed comparable in terms of validation, the method proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
2
27
1
1
Order By: Relevance
“…This step generally represents the easiest task and is well described in the (forensic) literature [13]. More recently proposed approaches focused on the analysis of ink volatile compounds, and mainly phenoxyethanol (PE) and its decrease over time [5][6][7][8][9][10][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. While gas chromatography coupled to mass spectrometry (GC/MS) was mainly used to analyse PE and other ink solvents, high performance liquid chromatography (HPLC) was also recently proposed to simultaneously analyse dyes and solvents [10,11,23].…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…This step generally represents the easiest task and is well described in the (forensic) literature [13]. More recently proposed approaches focused on the analysis of ink volatile compounds, and mainly phenoxyethanol (PE) and its decrease over time [5][6][7][8][9][10][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. While gas chromatography coupled to mass spectrometry (GC/MS) was mainly used to analyse PE and other ink solvents, high performance liquid chromatography (HPLC) was also recently proposed to simultaneously analyse dyes and solvents [10,11,23].…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…This is consistent with ndings in previously mentioned studies, which found that ageing rates are at least partially dependent on the initial ink composition, such as the volatility of solvents or the stability of the various dyes and pigments. [24][25][26] Projection of the aged inks onto the original PCA scores plot gives a clear visual indication of these changes, as well as the different ageing rates (Fig. 3).…”
Section: Characterisation Of Naturally Aged Samplesmentioning
confidence: 99%
“…[20][21][22][23] The precise rates at which these processes occur are highly dependent on a number of factors, including the initial ink composition, paper type and storage conditions. [24][25][26] This poses a signicant challenge to document examiners when attempting to compare ink entries of different ages, as ink from the same pen may give rise to very different spectral proles.…”
Section: Introductionmentioning
confidence: 99%
“…Dating research has already been conducted for different types of forensic marks (e.g. ink, gunshot residue and blood) and different interpretation models were proposed in the literature based on decision thresholds [126][127][128][129], trend tests [130,131], regression calculations [60,115,132] or likelihood ratios [130,133,134]. Concerning fingermarks, aging models based on regression calculations [71,107], likelihood ratios [107,120] and PCA [107,111,112] were reported in the literature.…”
Section: Interpretation Models and Validationmentioning
confidence: 99%